The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acsanm.2c05051
|View full text |Cite
|
Sign up to set email alerts
|

Improving Contacts and Electrical Performances of Nanofilms of MoS2 Transistors through Ultrastrong vdW Integration with Dirac Semimetal PtTe2

Abstract: Semiconductor−metal contacts as one major challenge have severely hindered the further progress of two-dimensional (2D) electronics.Here, we present a simple and effective strategy to improve the contacts and electrical performances by fabricating van der Waals (vdW) heterostructures with 2D semiconductor MoS 2 and type-II Dirac semimetal PtTe 2 . The semiconductor MoS 2 and Dirac semimetal PtTe 2 nanoflakes are synthesized through CVD routes separately, followed by systematic material characterizations to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The I on is still comparable to that of other TFETs even when the bias is reduced to be as small as 10 –3 V. We note that most inorganic TFETs operate under bias in the range of 0.5–1 V. While various strategies were proposed to lift the I on in TFETs, , the I on under lower bias is even orders of magnitude smaller than that under the normal bias (0.5–1 V). , As such, our results strongly suggest that the double-layer OTFET designed here is very promising for the LP application. Moreover, it is also instructive to compare our results with other novel heterojunction devices. , For instance, the SS of heterojunction FETs, such as those based on IGZO (indium–gallium–zinc oxide) and kagome lattice Si, is usually above 70 mV/dec, which is much higher than that of the double-layer OTFET in this work. It demonstrates that the low-SS characteristic of TFET is retained in the proposed OTFET because of the highly conductive 2D COFs employed in the devices.…”
Section: Results and Discusstionmentioning
confidence: 68%
“…The I on is still comparable to that of other TFETs even when the bias is reduced to be as small as 10 –3 V. We note that most inorganic TFETs operate under bias in the range of 0.5–1 V. While various strategies were proposed to lift the I on in TFETs, , the I on under lower bias is even orders of magnitude smaller than that under the normal bias (0.5–1 V). , As such, our results strongly suggest that the double-layer OTFET designed here is very promising for the LP application. Moreover, it is also instructive to compare our results with other novel heterojunction devices. , For instance, the SS of heterojunction FETs, such as those based on IGZO (indium–gallium–zinc oxide) and kagome lattice Si, is usually above 70 mV/dec, which is much higher than that of the double-layer OTFET in this work. It demonstrates that the low-SS characteristic of TFET is retained in the proposed OTFET because of the highly conductive 2D COFs employed in the devices.…”
Section: Results and Discusstionmentioning
confidence: 68%
“…The most straightforward integration method to form a m-TMD/TMD vdW contact is the transfer of m-TMD thin flakes onto the target TMD. This strategy has been extensively employed, resulting in the selection of various m-TMD categories, including degenerately doped TMDs, distorted structure (T′) TMDs, and intrinsic m-TMDs, as vdW contacts to TMDs.…”
Section: D Metals As Vdw Contactmentioning
confidence: 99%
“…Furthermore, as an important member of the 2D material library, the variety of intrinsic m-TMDs provides potential options as vdW electrodes for various TMDs. To date, several m-TMDs, such as NbS 2 , , NbSe 2 , VS 2 , VTe 2 , TaS 2 , PtSe 2, , PtTe 2 , NiTe 2 , CoS 2 , and ZrTe 2 , have been used as electrodes to achieve high-performance transistors. For example, a WSe 2 transistor with NbSe 2 contacts exhibited linear output characteristics even at 77 K, as well as MIT behavior and phonon-limited mobility, indicating the near electrical transparency of the WSe 2 contacts (Figure k–n).…”
Section: D Metals As Vdw Contactmentioning
confidence: 99%
“…2 For example, several studies have reported the successful formation of ohmic contacts by using vdW and semimetallic TMDCs. 29,30 Notably, most of these approaches are based on transfer-based methods or on the susceptibility of semimetals when exposed to ambient and harsh conditions. 24 These aspects may not be compatible with currently used semiconductor industrial-scale processes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Owing to the low density of states near the charge neutrality level, the semimetals could minimize the generation of MIGS, ultimately achieving low SBH and realizing ohmic contact behavior. ,, Consequently, the vdW and semimetallic contacts can be powerful tools for realizing an atomically clean and electronically sharp metal–TMDC interface with minimized gap states and tunable barrier heights . For example, several studies have reported the successful formation of ohmic contacts by using vdW and semimetallic TMDCs. , Notably, most of these approaches are based on transfer-based methods or on the susceptibility of semimetals when exposed to ambient and harsh conditions . These aspects may not be compatible with currently used semiconductor industrial-scale processes.…”
Section: Introductionmentioning
confidence: 99%